(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
In order to increase citizens’ engagement in the democratic process in Karnataka, the Systematic Voter Education and Electoral Participation (SVEEP) program has played a crucial role. The 2018 General Assembly elections were the focus of this study, which analyzes the transformational journey of SVEEP and its effects on varied constituency involvement, voter registration, and turnout. To overcome obstacles like disinformation and geographical inaccessibility, qualitative findings highlight the efficacy of merging mass knowledge with local facilitation. The research shows that democratic procedures, voter participation, and inclusion may all be greatly improved with well-planned voter education initiatives. One of the department’s top officials acts as a go-between for the media, keeping them apprised of breaking news that must be made public as soon as possible. On top of that, they’re lending a hand with the creation of audio and video tracks as well as the imaginative designs for campaign materials. Motivating citizens to cast their ballots in the next assembly election is an important responsibility of the Department of Information and Public Relations. In addition to traditional mass media, DIPR employs innovative outdoor media options to educate the electorate. Even though the option to "not agree" is available on electoral voting machines, 55% of people are unaware that it exists. The availability of Braille provision on EVMs is unknown to 63.4% of respondents, while 72.4% are unaware of VVPAT.